2006
DOI: 10.1007/s10661-006-9320-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of Volatile Organic Compounds from a Community-Based Air Toxics Monitoring Network in Deer Park, Texas, USA

Abstract: In the summer of 2003, ambient air concentrations of volatile organic compounds (VOCs) were measured at 12 sites within a 3-km radius in Deer Park, Texas near Houston. The purpose of the study was to assess local spatial influence of traffic and other urban sources and was part of a larger investigation of VOC spatial and temporal heterogeneity influences in selected areas of Houston. Seventy 2-h samples were collected using passive organic vapor monitors. Most measurements of 13 VOC species were greater than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 23 publications
(31 reference statements)
4
17
0
Order By: Relevance
“…Our investigation, as in previous studies (Pankow et al, 2003;Smith et al, 2007), demonstrated that members of the BTEX group of VOC are highly correlated, suggesting that it may be possible to monitor for only one or a few of these VOC when developing an air quality index for an exposure estimate.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our investigation, as in previous studies (Pankow et al, 2003;Smith et al, 2007), demonstrated that members of the BTEX group of VOC are highly correlated, suggesting that it may be possible to monitor for only one or a few of these VOC when developing an air quality index for an exposure estimate.…”
Section: Discussionsupporting
confidence: 82%
“…Another case study of exposure monitoring included a spatial analysis of VOC, carried out in Deer Park, TX, to assess the influence of traffic and other urban sources on VOC concentrations across the selected area. This study pointed to strong correlations between specific VOC and also showed an effect of wind direction on VOC concentrations (Smith et al, 2007). A comprehensive study of 88 VOC at 13 semirural to urban U.S. locations demonstrated that the members of the BTEX group (benzene, toluene, ethylbenzene, and xylenes) are highly correlated with one another (Pankow et al, 2003), suggesting that the primary contributors of these pollutants are mobile sources.…”
mentioning
confidence: 63%
“…3 Comparison of the canister VOC concentrations and the OVM VOC concentrations for the entire study period for benzene (a) and toluene (b) the BTEX compounds, which were consistently about twice as high (Mukerjee et al 2004). Median concentrations of BTEX compounds and the trimethylbenzenes measured outside ten homes in an urban residential subdivision near Houston (Deer Park) during the summer agreed well with the range of concentrations reported here for the Old Reservation and the New Reservation during the warm season, although the median levels of the alkanes (pentane and hexane) were two to three times higher (Smith et al 2007). Seasonal-specific median concentrations measured outside 100 homes in the Houston area, which included some neighborhoods in the vicinity of petrochemical facilities, were also in general agreement with the current results for the BTEX compounds, but concentrations of the chlorinated VOCs (trichloroethylene, tetrachloroethylene, methylene chloride, and p-dichlorobenzene) were higher, possibly due to the influence of the industrial sources (Weisel et al 2005b).…”
Section: Statistical Analysis Of Ovm Measurementssupporting
confidence: 74%
“…The OVM has been validated in other studies under controlled and ambient conditions in this urban area and elsewhere (Mukerjee et al 2004;Stock and Morandi 1996;Morandi and Stock 1997;Chung et al 1999a, b;Stock et al 1999;Pratt et al 2005;Stock et al 2008) and has been used extensively for the evaluation of spatial and temporal concentration variation of VOCs (Sexton et al 2004;Stock et al 2005;Weisel et al 2005a, b;Smith et al 2007;Chung et al 2009). The sampling strategy for this study consisted of ten 72-h sampling periods (Stock et al 2008), with five during the warm season and five during the cool season.…”
Section: Passive Monitoringmentioning
confidence: 99%
“…Oil refining is associated with emitting volatile organic compounds, mainly hydrocarbons, into the atmosphere, originated from the production processes, storage tanks, transport pipelines, and waste area (Kalabokas et al 2001;Cetin et al 2003;Rao et al 2007). VOC levels around the chemical and petrochemical industry (Kalabokas et al 2001;Cetin et al 2003;Navazo et al 2003;Lin et al 2004;Zhao et al 2004;Gariazzo et al 2005;Srivastava et al 2005;Hung-Lung et al 2007;Ras-Mallorquí et al 2007) and in urban atmospheres (Bomboí et al 2002;Navazo et al 2003;Fernández et al 2004Fernández et al , 2005Zhao et al 2004; Baroja et al 2005;Papadopoulos et al 2005;Srivastava et al 2005;Han and Naeher 2006;Geng et al 2007;Guo et al 2007;Hung-Lung et al 2007;Martins et al 2007;Molina et al 2007;Ras-Mallorquí et al 2007;Sather and Cavender 2007;Smith et al 2007) have been studied. The main source of VOCs in urban areas is road traffic and other combustion processes, and fuel evaporation.…”
Section: Introductionmentioning
confidence: 99%